RUSSIAN AS A FOREIGN LANGUAGE IN COMMUNICATIONS (American Journal of Interdisciplinary Research and Development, 2023)
At the present stage of development of our society, when numerous cultural connections arise everywhere, a redistribution of values, guidelines and motivations in the education system inevitably occurs. A universal approach to the development education system is training in intercultural communication. The very concept of intercultural communication implies equal cultural interaction between representatives of various linguistic and cultural communities, taking into account their originality, which leads to the need to identify what is universal on the basis of a comparison of foreign language and one’s own cultures. The subject of our research is the process of formation of communication in teaching Russian as a foreign language in institutes and universities. The purpose of the article is to reveal the content and identify the features of communication in the educational environment.